DETEKSI TRANSMISI TRANSOVARIAL VIRUS DEN-3 PADA NYAMUK Aedes aegypti DENGAN TEKNIK IMUNOSITOKIMIA MENGGUNAKAN ANTIBODI DSSE10 - Tri Wahono; Sitti Rahmah Umniyati (SPIRAKEL, 2018)
Transovarial transmission is a phenomenon as a supporting factor for the maintenance the presence of dengue virus in an area. Vector surveillance is an effort to control dengue disease. In addition to larvae surveillance, viral surveillance carried out on adult Ae. aegypti mosquitoes can actually be used for early warning systems for dengue outbreaks. DEN 3 virus antigen detection using streptavidin biotin peroxidase complex (SPBC) immunocytochemical technique is an alternative method for vector surveillance. The study aimed to prove the existence of transovarial transmission by detecting DEN 3 virus antigen in F1 generation mosquitoes from Ae. aegypti which has been infected orally. The study design was experimental. Adult Ae. aegypti female is infected with DEN 3 virus orally then mosquitoes are allowed to run their gonotrophic cycle. The resulting egg was colonized until becoming adult mosquitoes and DEN 3 virus antigen was detected. Antigen detection using SPBC immunocytochemical technique with DSSE10 monoclonal antibody on mosquito head squash preparation in 4 and 16 days old mosquitoes. The results were analyzed descriptively. Streptavidin biotin peroxidase complex (SBPC) immunocytochemical technique can detect DEN 3 virus antigens indicated by the presence of brown color in the head squash preparation. The presence of the DEN 3 virus antigen also proves the presence of transovarial transmission in infected Ae. aegypti mosquitoes which has been infected orally.